Right to Freedom of Religion: A Gendered Difference - Stuart, Alison (Wydawnictwo Naukowe UAM, 2015)
This article critically analyses European jurisprudence to ascertain the extent to which the right to freedom of religion has been interpreted as a right of religion to internal autonomy. It asserts that women are being denied an effective right to freedom of religion insofar as they are unable to directly influence the content or structure of their religion. It argues that to fulfil women’s equal right to freedom of religion, women’s power and position within religion must be equivalent to men’s. It therefore asserts that an intrinsic part of States’ obligation to secure the right to freedom of religion is the facilitation of gender equality within religion. The article culminates by proposing proportionate and appropriate methods to facilitate gender equality within religion.
Keywords: Gender Equality; Freedom; Religion